Foresight Strategy Analysis in Strategic DecisionMaking Head of School in State Middle School 1 City of Gorontalo (Journal of Pedagogical Inventions and Practices, 2022)
This study aims to 1) describe the strategic decision making of the principal of SMA Negeri 1 Gorontalo, 2) describe the foresight strategy of the principal of State Senior High School 1 Gorontalo City. The approach used in this study uses a qualitative approach with the type of case study research. Data collection techniques in this study using interviews, observation and documentation. As for the results in this study, there are several programs and strategies carried out to meet the aspects of the foresight strategy because the principal of State Senior High School 1 Gorontalo shows a plan or goal to be achieved so that alternative choices are determined based on the right information, speed and accuracy of the procedures and approaches used in the decision-making process. decisions based on the suitability of internal and external conditions as well as follow-up to the implementation of decisions in schools.